TISSUE-SPECIFIC RECOVERY OF PHENOLICS IN CLINACANTHUS NUTANS UNDER PRESSURIZED HOT WATER EXTRACTION: A COMPARATIVE STUDY OF LEAVES VERSUS STEMS (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
Background: Clinacanthus nutans is recognized for extracts rich in phenolics and flavonoids, exhibiting noteworthy antioxidant and anti-inflammatory activities. Under pressurized hot water extraction (PHWE)—a green, water-only technique—both extraction settings and the specific plant tissue significantly influence the yield and integrity of these phytochemicals.Methods: We executed a head-to-head comparison of leaves and stems under unified PHWE screening parameters: 120 °C, 20 min, 2 g of sample in 50 mL of water, with a particle size of
Keywords: Clinacanthus nutans; subcritical water; phenolics; flavonoids; antioxidant activity; tissue comparison.